O discurso da sustentabilidade no processo de planejamento público participativo: um estudo à luz da teoria Habermasiana - Flores, Aline Pires (2015)
This study discusses the discursive construction process in a political public sphere intended for the planning and management of the Agenda 21 for Paraná. This represents the local layer of the global agreement signed by 179 nations at the time of Rio-92 for the establishment of common goals of global development for the 21st century, which considers, with the economic dimension, environmental limits and social injustices. Based on the critical theory of Habermas and assuming a counter-hegemonic posture from that observed in the mainstream of the Brazilian Academy of Administration, the central argument is that the sustainability discourse is subject to mechanisms of coercion and system domination, which hinder the establishment of legitimate agreements that would bring about an emancipated society. In this sense, the aim of the study was to uncover how the mechanisms in this public sphere operate, in time for the public participatory planning of sustainability in the context of Paraná, in the light of Habermas’ theory of communicative action. Since a qualitative approach is taken to the present research, its empirical component features ideographic procedures, aiming to keep an epistemological consistency in relation to the theoretical framework. The principal evidence demonstrates that, despite the strengthening of a participatory democratic model in the direction of sustainable development that the forum represents, the orientation in its communicative processes reflects the strategic interests of dominant groups. Such interests prevent this sphere of public deliberation from fostering integral and autonomous communicative action. This being so, we might infer that the sustainability discourse produced by the forum does not express the voices of all groups in society. In this sense, we highlight the disregard of the interests of the traditional communities, which historically have been more vulnerable to the consequences of developmental models. The conclusion of the study is that two coercive forces stand out. The interests of private initiatives characterize the first, where the absence from the debate of the companies and institutions that represent them weakens the plurality required in a deliberative democratic process of public policies on sustainability. The role of the State shows up the second; this role demonstrates the interest by its control over the social processes of participation by formal authority, even keeping the forum within the physical limits of its structure. Besides, the representatives of the State act to restrict the application of resources through which the forum would otherwise expand its penetration, impeding a wider participation by the society of Paraná state.